MOTIVASI INDONESIA BEKERJASAMA DENGAN VIETNAM DI BIDANG PERIKANAN TAHUN 2010-2012 - Puji Lestari; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study used a qualitative research method that the source data is takenfrom books , journals , newspapers , the internet , and previous studies have data thatis relevant to the title . Perspectives and levels of analysis used in this study is that thestate as the main actor . By using the theory of international cooperation and analyzesthe state of the nation . This study will describe the motivations that made Indonesianfisheries cooperation with Vietnam . And knowing the interests of Indonesian fisheriescooperation with Vietnam . Indonesia as a country with high potential fishery resourcesare threatened by illegal fishing, which often occur in the waters of Indonesia andneighboring countries especially Vietnam . So expect the cooperation that exists toprevent and reduce iilegal fishing that occurs in both countries as well as the fisheriesco-operation can improve Indonesia and Vietnam export fisheries and mutuallybeneficial cooperation between the two countries that is .Keywords : Motivations, Relation Cooperation, Fisheries, Illegal Fishing, Vietnam